Nine actions to successfully restore tropical agroecosystems - Michael David Pashkevich; Francisco d’Albertas; Anak Agung Ketut Aryawan; Damayanti Buchori; Jean-Pierre Caliman; Adrian David González Chaves; Purnama Hidayat; Holger Kreft; Mohammad Naim; Appolinaire Razafimahatratra; Edgar Clive Turner; Zemp, Clara; et al. (My University, 2022)
Well-designed approaches to ecological restoration can benefit nature and society. This is particularly the case in tropical agroecosystems, where restoration can provide substantial socioecological benefits at relatively low costs. To successfully restore tropical agroecosystems and maximise benefits, initiatives must begin by considering ‘who’ should be involved in and benefit from restoration, and ‘what’, ‘where’, and‘how’ restoration should occur. Based on collective experience of restoring tropical agroecosystems worldwide,we present nine actions to guide future restoration of these systems, supported by case studies that demonstrate our actions being used successfully in practice and highlighting cases where poorly designed restoration has been damaging. We call for increased restoration activity in tropical agroecosystems during the current UN Decade on Ecosystem Restoration.